Conocimiento sobre responsabilidad social universitaria en estudiantes del quinto nivel de educación primaria facultad de ciencias de la educación y humanidades UNAP 2021 - Tuesta Tangoa, Ruth Nancy (2024)
The object of study was to investigate the knowledge of university social responsibility of students at the last level of Primary Education, Faculty of Education Sciences and Humanities, Iquitos-2021, a basic type of research was carried out, descriptive, the selected sample were 42 students selected by the non-probabilistic method. It was found that 90.6% of students in the fifth level of Primary Education of the Faculty of Education have a good level of understanding about university social responsibility. In addition, he identified that 82.4% have a good level of knowledge about the responsible campus dimension, 91.8% also identify knowledge about categories of professional training and citizenship and social development of knowledge respectively, 95.3% show a good level of social participation. In conclusion, universities assume in one of their commitments to be an active part of the social context that surrounds it with the effective practice of university social responsibility and to have a positive impact on the community.